Thasian black-figure pottery in the archeological context: a methodological proposal - Hora, Juliana Figueira da (Revista do Museu de Arqueologia e Etnologia, 2023)
This study explores an archaeological contextual analysis method applied to a sample of black-figure pottery from the archaic period discovered at Thassos, an island located in the Northern Aegean. This material was found in sanctuaries devoted to female deities, but mostly in the Artemision, located in Limenas, ásty of the polis. The method contributed to further our archeological understanding of the areas where the black-figure pottery fragments were documented, cataloged by Anne Coulié in the 2002 publication La céramique thasiennes à figure noires. We will also present our main tools for assembling the documentary corpus. This study of ceramics had the specific character of highlighting information contained in the excavation report, dynamizing our reading of the spaces, landscape, and local history to better understanding that society. This methodology brought about intense and extensive aspects during the discussions.